KESETARAAN HAK PENYANDANG DISABILITAS DALAM KEBIJAKAN PEMERINTAH DAERAH DKI JAKARTA (Studi Perda Nomor 10 Tahun 2011 tentang Perlindungan Penyandang Disabilitas) - Muhammad Faisal (2021)
This study aims to analyze the legal protection and equal rights of Persons with Disabilities in state and local government policies in Indonesia. This research focuses on the implementation and implementation of regulations regarding the protection of equal rights for persons with disabilities, especially in DKI Jakarta. Equality rights for disability are divided into accessibility rights and the right to get equal treatment in the economic field. This study aims to test the effectiveness of existing regulations with the reality that occurs in the field. This study is a qualitative research with a juridical normative approach with a statutory approach. The data sources used are primary data sources, namely using Law Number 8 of 2016 concerning Persons with Disabilities, DKI Jakarta Regional Regulation Number 10 of 2011 concerning Protection of Persons with Disabilities and Minister of Social Affairs Regulation No. 18 of 2018 as well as secondary and tertiary data sources. This study shows that the regulations established by the authorities can still be said to be not fully implemented in the field so that the ideals of the nation who want to create a friendly and inclusive country for all its citizens, especially Persons with Disabilities, have not been fulfilled. Keywords: Equality of Rights, Persons with Disabilities, Government Policy, DKI Jakarta